2022
DOI: 10.3390/diagnostics12112862
|View full text |Cite
|
Sign up to set email alerts
|

Results of Numerical Modeling of Blood Flow in the Internal Jugular Vein Exhibiting Different Types of Strictures

Abstract: The clinical relevance of nozzle-like strictures in upper parts of the internal jugular veins remains unclear. This study was aimed at understanding flow disturbances caused by such stenoses. Computational fluid dynamics software, COMSOL Multiphysics, was used. Two-dimensional computational domain involved stenosis at the beginning of modeled veins, and a flexible valve downstream. The material of the venous valve was considered to be hyperelastic. In the vein models with symmetric 2-leaflets valve without ups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…In reality, they exhibit different levels of elasticity and movability. In our other in silico study, we demonstrated that there is a dynamic interplay between stenoses located upstream and valves located downstream, and that a relevant stenosis changes the valve geometry to the unfavorable one [46]. Thirdly, flow volume measurements using the "probes" were not very precise.…”
Section: Discussionmentioning
confidence: 78%
“…In reality, they exhibit different levels of elasticity and movability. In our other in silico study, we demonstrated that there is a dynamic interplay between stenoses located upstream and valves located downstream, and that a relevant stenosis changes the valve geometry to the unfavorable one [46]. Thirdly, flow volume measurements using the "probes" were not very precise.…”
Section: Discussionmentioning
confidence: 78%
“…Actually, they exhibit different levels of elasticity and movability. In our another in silico study, we demonstrated that there is a dynamic interplay between stenosis located upstream and the valve located downstream, and that a relevant stenosis changes the valve geometry to the unfavorable one [35]. Thirdly, flow volume measurements using the "probes" were not very precise.…”
Section: Discussionmentioning
confidence: 85%
“…The flows in the right and left jugular veins were considered the same and equal to half of the total flow in the superior vena cava. This simplification is justified by the scarcity of data in the literature, by the absence of consensus regarding the flow values in the right and left jugular veins [28,29] and the possible similarity of the flow values between those two veins . As a boundary condition at the outlet of the superior vena cava, the pressure curve in the right atrium was adopted from to Mynard JP, Smolich JJ (2015) [27].…”
Section: Boundary Conditionsmentioning
confidence: 99%